2006
DOI: 10.4049/jimmunol.176.5.2958
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Terminal Flanking Residues Determine the Conformation of a Peptide–Class II MHC Complex

Abstract: The peptide spanning residues 48–62 of hen egg white lysozyme presented by I-Ak molecules gives rise to two T cell populations, types A and B, that recognize distinct conformers of the complex generated in late and recycling endosomes. The class II–like accessory molecule H2-DM functions as a conformational editor, eliminating the type B conformer in late endosomes. Here, we show that the conformation of the complex, and its susceptibility to editing by H2-DM, are determined by peptide amino-terminal flanking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…If DM were absent or inactive in these vesicles, or if the rate of transit through the pathway overwhelmed the capacity of DM to function as a conformational editor, then presentation of the type B conformer would be the expected result. Alternatively, phagolysosomal proteases may preferentially generate truncated peptides that lack flanking residues necessary for DM to eliminate the type B conformer; this would result in presentation of the type B conformer, as the complexes that form would be resistant to the editing function of DM (31).…”
Section: Discussionmentioning
confidence: 99%
“…If DM were absent or inactive in these vesicles, or if the rate of transit through the pathway overwhelmed the capacity of DM to function as a conformational editor, then presentation of the type B conformer would be the expected result. Alternatively, phagolysosomal proteases may preferentially generate truncated peptides that lack flanking residues necessary for DM to eliminate the type B conformer; this would result in presentation of the type B conformer, as the complexes that form would be resistant to the editing function of DM (31).…”
Section: Discussionmentioning
confidence: 99%
“…This activity of H2-DM (and DMY) is likely to affect T cell responses to a large array of natural peptides with Nterminal extensions. In contrast, as shown for HEL, some short synthetic peptides devoid of N-terminal extensions will exist in both type A and B conformations independent of the presence of DM (10). We can speculate that in physiological conditions, professional APCs in the tumor environment will process exogenous TAAs and load nominal peptides in the context of DM, thereby eliminating type B complexes.…”
Section: Discussionmentioning
confidence: 86%
“…DMY reduced the display of type B HEL-I-A k conformers at the cell surface of APCs, causing the poor stimulation of CP1.7 and MLA11.2 type B T cell hybridomas. Unanue and collaborators (10) showed that HEL 48-61 binds MHC II in at least two different conformations depending on the folding of the N-terminal extension, especially at position -2. One of these conformers (type B) is nonoptimal, and thus readily dissociates in the presence of H2-DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations